Waste Management in Green Building Operations Using GSCM - Camgöz Akdağ, Hatice; Beldek, Tuğçe (International Journal of Supply Chain Management, 2017)
Green buildings also known as green construction or sustainable building are environmentally responsible and resource-efficient throughout a buildings life-cycle: from siting to design, construction, operation, maintenance, renovation, and demolition. Today the environmental issues and the concern for sustainability is encouraging more effective and efficient usage of energy, water and material currently used, ensure the prevention of any kind of waste, perform environmentally sensible and eco-friendly building design and be environmentally friendly in the process of construction. Environmental problems and the growth of construction industry cause a new topic to manage construction waste with the help of green supply chain management (GSCM). This requires close cooperation of the design team, the architects, the engineers, and the client at all project stages. GSCM reduces energy usage and waste, so it prevents any problem that will occur in human health and environment. This paper aims to combine the architects green building operations together with the engineers green supply chain management for both reducing the usage of materials, encouraging more effective and efficient usage of energy, water and material currently used, ensure the prevention of any kind of waste, perform environmentally sensible and eco-friendly building design and to be able to reuse, recycle, or recover the waste. The European Union Council published a waste management directive in 2008 that gives some goal numbers to manage construction waste to minimize the environmental effect. The goal is to reach a reduction of 70% of construction and demolition waste (CDW) that will be reused, recycled or recovered in 2020. The aim of this paper is to explore the cost-benefit and social-benefit reflections by the combination of these two techniques, based on the literature review and case study examples from Turkey a model is built and propositions regarding Green Building operations using GSCM and reverse logistics are formulated.